Application Paclobutrazol and Duration of Drought Stress to Flowering Induction in Chokun Orange - Zulfa Rahmadita Nur Azizah; Sakhidin Sakhidin; Saparso Saparso; Agus Sarjito (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Induction of flowering is one of the efforts that can extend the production period of Chokun oranges. This study aims to determine the effect of the dose of paclobutrazol (PBZ), duration of drought stress and the combination of treatments that gives the best results on the Chokun orange (Citrus sp.). The research design used was randomized complete block design (RCBD), consisting of 3 replications. The treatment in this study was a combination of the dose of PBZ (control, active ingredient 0.75 g plant-1 and active ingredient 1.5 g plant-1) and duration of drought stress (control, 1, 2 and 3 weeks). The results show that the application of PBZ and duration of drought stress can induce the flowering of citrus plants as seen from the generative shoot variables with a quadratic model on the equation y = -17.778x2 + 31.556x + 26.667 at the optimum dose of 0.89 g plant-1 of active ingredient and 1 week of drought. The dry period of 3 weeks gives the best results seen from variables of the number of flowers and number of fruits. In general, the results suggest that the application of PBZ and duration of drought stress can transfer from the vegetative phase to the generative phase which in turn could induce the flowering of citrus plants.